A Mid-IR Optical Parametric Oscillator Pumped by an Actively Q-Switched Ho:YAG Ceramic Laser*Supported by the National Natural Science Foundation of China under Grant Nos 61308009, 61405047 and 50990301, the Fundamental Research Funds for the Central Universities under Grant Nos HIT.NSRIF.2014044 and HIT.NSRIF.2015042, and the Science Fund for Outstanding Youths of Heilongjiang Province under Grant No JQ201310. (August 2015) - Yuan, Jin-He; Duan, Xiao-Ming; Yao, Bao-Quan; Li, Jiang; Shen, Ying-Jie; Cui, Zheng; Dai, Tong-Yu; Pan, Yu-Bai
<x content-type="archive" xml:space="preserve">Abstract</x> We demonstrate a mid-IR ZnGeP2 (ZGP) optical parametric oscillator (OPO) pumped by a dual-end-pumped actively acousto-optic Q-switched Ho:YAG ceramic laser. The maximum average output power of 35 W is obtained at a pulse repetition frequency of 20kHz from the Ho:YAG ceramic laser. Under the maximum incident pump power of Ho:YAG ceramic laser, the maximum output power of 14 W is obtained from the ZGP OPO, corresponding to the slope efficiency of 49.6% with respect to the incident pump power. The wavelength can be tuned from 3.5 μm to 4.2 μm (signal), corresponding to 5.2–4.1 μm (idler). The beam quality M2 is less than 2.3 from the ZGP OPO.